Pengembangan Multimedia Interaktif dengan Example Non Example Berbasis Inkuiri pada Pembelajaran IPA Materi Organ Pencernaan Hewan untuk Siswa Kelas V - Lisa Sri Wijayanti; Irwan Koto; Endang Widi Winarni (Universitas Bengkulu, 2023)
This study aims to develop interactive multimedia with non-example-based examples of inquiry-based science learning on animal digestive organs for class v students, especially the dimensions of process, product, and application. The type of research used was the research and development (Rh & D) with the 4D model (Define, Design, Development, and Disseminate). Because of the COVID-19 pandemic, the research, and development stage performed in three stages without the Disseminate stage. The research instrument was the questionnaires, interview guidelines, and validation sheets. Validated aspects include the appropriateness of the material, language, and appearance. The validators who validated the media aspects consisted of lecturers and teachers. The user responses were from the responses of 20 fifth-grade students and one teacher. Based on the research and discussion results, it was concluded that interactive multimedia with non-example based on inquiry was very appropriate for learning science content on theme 3 Healthy Food, material for animal digestive organs.